The Contribution of Kalam in Resolving Contemporary Theological Controversies: A Study of Rational Debates - Ali Mufron; Sofia Lim; Rachel Chan; Jasafat Jasafat (Yayasan Adra Karima Hubbi, 2025)
The discipline of Kal?m (Islamic theology) has historically served as a framework for addressing theological controversies, utilizing rational discourse to harmonize scriptural interpretation with intellectual inquiry. In the modern era, theological debates concerning issues such as faith, ethics, and the reconciliation of science and religion have intensified, necessitating renewed exploration of Kal?m as a method for resolving these challenges. This study examines the contribution of Kal?m in addressing contemporary theological controversies through rational debates and intellectual engagement. A qualitative approach was employed, combining historical analysis and textual study of classical Kal?m works with case studies of modern applications in theological discourse. Data were collected through critical analysis of primary texts and interviews with contemporary theologians and scholars actively engaging in rational debates on theological issues. The findings demonstrate that Kal?m provides a robust intellectual foundation for navigating contemporary theological controversies. Its emphasis on rational argumentation fosters constructive dialogue between traditional Islamic perspectives and modern intellectual paradigms. The study concludes that Kal?m remains a vital tool for resolving contemporary theological controversies, bridging the gap between tradition and modernity.